Accounting for functional loss in Alzheimer's disease and dementia with Lewy bodies: Beyond cognition. Issue 2 (15th July 2013) - Hamilton, Joanne M.; Salmon, David P.; Raman, Rema; Hansen, Lawrence A.; Masliah, Eliezer; Peavy, Guerry M.; Galasko, Douglas
Abstract: Background: The relative contributions of cognitive, motor, and behavioral deficits to the impairment of physical or instrumental activities of daily living (ADLs) may differ in patients with dementia with Lewy bodies (DLB) and Alzheimer's disease (AD). Methods: Multiple linear regression analyses were used to identify the amount of variability in physical self‐maintenance and instrumental ADL ratings predicted by cognitive, motor, and behavioral indices separately for patients with autopsy‐diagnosed DLB (n = 39) or AD (n = 39). Results: Motor dysfunction accounted for significant variance in physical ADLs in DLB ( R 2 change = 0.17), whereas behavioral ( R 2  change = 0.23) and motor dysfunction ( R 2 change = 0.13) accounted for significant variance in AD. Motor ( R 2 change = 0.32) and cognitive ( R 2 change = 0.10) dysfunction accounted for significant variance in instrumental ADLs in DLB, whereas cognitive ( R 2 change = 0.36) and behavioral ( R 2 change = 0.12) dysfunction accounted for significant variance in AD. Conclusions: Cognitive, motor, and behavioral deficits contribute differently to ADL changes in DLB and AD. Thus, treatments designed to ameliorate a certain aspect of AD or DLB (e.g., cognitive dysfunction) may have a larger impact on everyday functioning in one disorder than the other.